Mannose-binding lectin is produced by vaginal epithelial cells and its level in the vaginal fluid is influenced by progesterone. - Bulla, R; De Seta, F; Radillo, O; Agostinis, C; Durigutto, P; Pellis, V; De Santo, D; Crovella, S; Tedesco, F (Mol Immunol, 2010)
Mannose-binding lectin (MBL) is a recognition molecule of the complement (C) system and binds to carbohydrate ligands present on a wide range of pathogenic bacteria, viruses, fungi, and parasites. MBL has been detected in the cervico-vaginal cavity where it can provide a first-line defence against infectious agents colonizing the lower tract of the reproductive system. Analysis of the cervico-vaginal lavage (CVL) obtained from 11 normal cycling women at different phases of the menstrual cycle revealed increased levels of MBL in the secretive phase. Part of this MBL derives from the circulation as indicated by the presence of transferrin in CVL tested as a marker of vascular and tissue permeability. The local synthesis of MBL is suggested by the finding that its level is substantially higher than that of transferrin in the secretive phase. The contribution of endometrium is negligible since the MBL level did not change before and after hysterectomy. RT-PCR and in situ RT-PCR analysis showed that the vaginal tissue, and in particular the basal layer of the epithelium, is a source of MBL which binds to the basal membrane and to cells of the outer layers of the epithelium. In conclusion, we have shown that MBL detected in CVL derives both from plasma as result of transudation and from local synthesis and its level is progesterone dependent increasing in the secretive phase of the menstrual cycle.
Keywords: Adolescent; Adult; Body Fluids; Enzyme-Linked Immunosorbent Assay; Epithelial Cells; Female; Humans; Immunohistochemistry; Mannose-Binding Lectin; Menstrual Cycle; Progesterone; Reverse Transcriptase Polymerase Chain Reaction; Vagina; Young Adult